2009
DOI: 10.1242/jcs.050625
|View full text |Cite
|
Sign up to set email alerts
|

Genetic evidence that the higher plant Rab-D1 and Rab-D2 GTPases exhibit distinct but overlapping interactions in the early secretory pathway

Abstract: GTPases of the Rab1 subclass are essential for membrane traffic between the endoplasmic reticulum (ER) and Golgi complex in animals, fungi and plants. Rab1-related proteins in higher plants are unusual because sequence comparisons divide them into two putative subclasses, Rab-D1 and Rab-D2, that are conserved in monocots and dicots. We tested the hypothesis that the Rab-D1 and Rab-D2 proteins of Arabidopsis represent functionally distinct groups. RAB-D1 and RAB-D2a each targeted fluorescent proteins to the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
60
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 55 publications
7
60
0
1
Order By: Relevance
“…GTPases were abundantly present in the SYP61 proteome (Supplementary information, Tables S1 and S2) including RABD2a and RABD2b, which have been shown to colocalize in the Golgi and TGN [33,34]. Likewise, we showed that RABD2b and SYP61 [35].…”
Section: Vesicle Tethering Components Of the Syp61 Compartmentsupporting
confidence: 61%
“…GTPases were abundantly present in the SYP61 proteome (Supplementary information, Tables S1 and S2) including RABD2a and RABD2b, which have been shown to colocalize in the Golgi and TGN [33,34]. Likewise, we showed that RABD2b and SYP61 [35].…”
Section: Vesicle Tethering Components Of the Syp61 Compartmentsupporting
confidence: 61%
“…We coexpressed mRFP-tagged wild-type RABA members with Venus-RABA4c N128I or Venus-RABA6a N126I for suppression activities for transport defects of FLS2 in tobacco cells expressing FLS2-GFP and CFP-SYP61. The inhibitory effects of NI mutants were specifically rescued by coexpression of their wild-type versions but not by the other RABA members, which again indicated specific inhibition of the distinct trafficking event by each mutant RABA, as is the case for other plant RAB GTPases (Figures 4C and 5C;Batoko et al, 2000;Kotzer et al, 2004;Pinheiro et al, 2009). We then examined the order of functions of two RABA members, RABA4c and RABA6a, in endocytic trafficking of FLS2 by double infiltration of their NI mutants.…”
Section: Raba6a and Raba4c Act In Distinct Steps Of Fls2 Endocytosismentioning
confidence: 78%
“…Similar to ER-Golgi trafficking, vesicle formation and movement as well as vesicle tethering and fusion are influenced by GTP-binding proteins of the ARF and Ras genes from rat brain (Rab) types. The expression of dominant-negative alleles encoding proteins that exhibit impaired GTP binding has shown that the activity of members of different Arabidopsis Rab subclasses is linked to distinct sorting events (Batoko et al, 2000;Pinheiro et al, 2009). Members of the Rab-E subclass in particular are implicated in post-Golgi trafficking to the plasma membrane, as indicated by Golgi retention of otherwise secreted cargo upon expression of RAB-E1 d (Zheng et al, 2005).…”
Section: From the Golgi To The Plasma Membranementioning
confidence: 99%